2011
DOI: 10.1007/s00424-011-0933-6
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in myofilament length-dependent activation

Abstract: The Frank-Starling law is an important regulatory mechanism of the heart that links the end-diastolic volume with the systolic ejection fraction. This beat-to-beat regulation of the heart, underlined at the cellular level by higher myofilament calcium sensitivity at longer sarcomere length, is known as length-dependent activation or stretch sensitization of activation. However, the heart is structurally and functionally heterogeneous and asymmetrical. Specifically, contractile properties are not uniform within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 107 publications
2
30
0
Order By: Relevance
“…The heart is known to manifest regional heterogeneity, with reports of transmural differences between the endocardium and epicardium in voltage-gated K ϩ currents (2), action potential duration (14), excitation-contraction coupling (7), myosin light chain kinase abundance (5), and myofilament properties (3,4,25). We have previously reported that ␣ 1 -ARs mediated fundamentally different inotropic responses in the RV versus LV myocardium (27,28).…”
Section: Discussionmentioning
confidence: 97%
“…The heart is known to manifest regional heterogeneity, with reports of transmural differences between the endocardium and epicardium in voltage-gated K ϩ currents (2), action potential duration (14), excitation-contraction coupling (7), myosin light chain kinase abundance (5), and myofilament properties (3,4,25). We have previously reported that ␣ 1 -ARs mediated fundamentally different inotropic responses in the RV versus LV myocardium (27,28).…”
Section: Discussionmentioning
confidence: 97%
“…Recent experimental data have shown heterogeneity in length dependence [31]. However, the implications of this effect on whole organ pump function are still unclear.…”
Section: Transmural Heterogeneitymentioning
confidence: 99%
“…Changes in such 'isoform' proportions over time have been observed across species in response to chronic cardiac stress [30], and the protein has also been implicated in ischaemic human heart disease [34]. Studies in recent years have uncovered more data on this important protein in experiments on both wild-type and genetically modified mice [22,31,35], although its functional role in the beating heart remains debated. Section 4.1 provides an example of an application of the VPM model to investigate the heterogeneity of tension generation in light of the previous experimental results and modelling predictions described in this section.…”
Section: Hypothesis Testing In the Mouse Heart Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the molecular mechanisms and cellular signal transduction processes that underlie these cellular regulatory systems are still under intense investigation [9]. In this issue, this area of research is reviewed by contributions from the groups of Campbell [5], Cazorla [6], Cingolani [7], Peter Kohl [2], Landesberg [23], and McDonald [16].…”
mentioning
confidence: 99%